Dinâmica folicular e avaliação de manipulação hormonal em bezerras nelore visando a produção in vitro de embriões - Zacarias, Thaís Abritta (2015)
The study of prepubertal bovine follicular dynamics and the reproductive management investigation for including these animals on in vitro embryo production (IVP) could be an alternative for accelerating genetic gain by reducing the generation interval. Follicular dynamics was monitored daily by ultrasound in ten Nelore calves (2-3 months of age), during 18 consecutive days. A successive anovulatory follicular wave-like pattern was identified, where until 3 follicular growth waves were detected with 31.4 ± 3.45 follicles and dominant follicles maximum diameter of 3.03 ± 0.17 mm. Additionally, a hormonal treatment for Ovum Pick Up (OPU)/IVP in 9 Nelore calves (4-7 months of age) were evaluated in a cross-over design. The treated group - TG (n=9. Progesterone, Estradiol Benzoate, FSH and LH) had the follicular population increased (20.0 ± 4.95 in D0 to 26.66 ± 4.24 in D7) as the follicles 2,5 mm number (4.11 ± 1.96 in D0 to 11.55 ± 4.09 in D7) and even the aspirated follicles number (95 vs 152, respectively for control group CG; n=9 and TG). However, the number of blastocysts in D7 (3 vs 9, respectively for CG and TG) and the number of embryos per donor (0.33 vs 1.0, respectively for CG and TG) were not increased by the treatment. In summary, despite the Nelore calves showed smaller follicular diameters, the follicular wave pattern and the number of follicles were similar to those results reported in Zebu females, in reproductive activity. The hormonal treatment increased the follicular population and the aspirated follicles number, but it was not verified that IVP was enabled by its use in those animals.